Identity as visibility: perspectives and experiences of Indigenous Peoples in Manitoba with racial, ethnic, and indigenous identifier data collection within healthcare. - Fowler-Woods, Amanda (2023)
Race, ethnicity, and Indigenous identity (REI) data collection, a strategy to address health and healthcare inequities, is emerging in Canada. Traditional teachings remind us to embrace our Indigenous identities. Yet, Indigenous identity within healthcare is often connected with racism, and mistreatment; an important context surrounding REI data. As Manitoba implements REI data collection at point of healthcare, reflecting on historical and current narratives surrounding REI data collection is beneficial. This dissertation advances collective knowledge of Indigenous understanding and experiences of REI data collection. As an Anishinaabekwe, researcher, and Manitoba REI team member, I bring experiential knowledge and relationships to this dissertation. Informed by the Contemporary Indigenous Empowerment Theory (CIET), this dissertation highlights relationships of power, social justice, and Indigenous identity/voices. A qualitative research design includes four methods identified below with key findings. Story-gathering with 20 self-identifying First Nations, Inuit, and Métis people in Manitoba opened space for Indigenous voices to inform our understanding of REI data collection and its impacts. Their meaning of Indigenous identity, experiences in healthcare, and perspectives on, and best practice for, REI data collection, informed how self-declaration of Indigenous identity is a highly complex matter. An environmental scan of REI data collection in Manitoba was guided by CIET to highlight relations of power, social justice, and Indigenous voices, deepening our knowledge of REI data collection. Creating awareness and evidence for health organizations, researchers, practitioners, patients, and the public to understand the current context of REI data collection in Manitoba. A scoping review examined how Indigenous identity, voice, and methodologies are upheld in health research. Findings suggest identity transparency of researchers and research participants requires strengthening and raising collective understanding ...